The Culture Policy for MSME in Digital and Their Prospects - Rudiatin, Endang (BASKARA : Journal of Business and Entrepreneurship, 2023)
The current era of digitalization forces entrepreneurs to change their marketing strategy from direct sales to online sales, either in whole or in part. However, the transition is not easy for micro, small, and medium-sized enterprises () because of the limitations of knowledge and facilities they have, so the process goes gradually. The study aims to find out the contribution of online marketing for micro-small enterprises to the resilience of enterprises during the restrictions that have lasted for two years. The study is also a policy recommendation against some digital policy directions against MSME by the Ministry of Informatics and Communications of the Republic of Indonesia. The research object is a member of  ISMEA (Indonesia Small Medium Enterprises Association), which meets the business age criteria of more than 2 years, actively performs hybrid sales (online and offline), and is able to survive during that time. Research methods are carried out qualitatively through descriptive, participatory observation. In-depth interviews were conducted with informants selected using snowball techniques. The results of the research found that online marketing on MSME is carried out through independent web hosting or through marketplace or e-commerce applications available or be used simultaneously. Self-marketing has the advantage that it does not require commission fees from the other party, so the entire profit becomes the seller's. However, it also has a weakness with its limited market accessibility as it requires costs to promote the site. While marketing through the marketplace has the advantages of the wide range of the market and the limitation of the promotion of the applicator, it also has disadvantages such as commission fees for applicators and price competition with providers of similar products or services in the same application or other applications. The conclusion obtained is that MSME is more familiar with using social media compared to the marketplace, in addition to the fact that web hosting is rarely used, even though it is free. The stages providing an appearance in the application require their own skills. While the direction of the marketing digitization policy on MSME that has been running for this time has begun to form a culture of marketing digitalization for micro and small enterprises, especially the use of the application for product delivery.